Canção para inglês ver: gêneros, identidades e relações de poder no carimbó e no brega - SILVA JUNIOR, Antonio Carlos Fausto da (Universidade Federal do Pará, 2017)
This Master’s Thesis is entitled Songs for the sake of the show: genres, identities and power relations in carimbó and brega, and it aims to analyze the meanings on cultural identities portrayed in carimbó and brega, two music genres promoted to the global market as authentic productions from the Pará state, northern Brazil. Our starting point for this work is the notion of communicative nature (MARTÍN-BARBERO, 2001) and the traits of communication process (FRANÇA. 2001) presented both by the carimbó and the brega. These notions help identify discursive strategies (CERTEAU, 2012) activated in the communication configuration of these music genres (JANOTTI JÚNIOR, 2006), so we are able to discuss meanings on cultural identities (HALL, 2011) based on these strategies. For that purpose, we use a) discourse analysis, and b) iconography and iconology, two research methods from the field of History of Art that provide the tools to work the discursive characteristics of the carimbó and the brega. The communication configuration of both genres is crossed by asymmetric relations of corporative, cultural and political power and foreshadows discursive strategies for the domestication of meanings on identities. These domesticated meanings, in their turn, are preferred in detriment of cultural hybridizations capable to stand as threat to the visibility of artists, producers, businessmen and politicians in a global market used to the consumption of regionalisms (HALL, 2011).